Crystalloid and Colloid Compositions and Their Impact - Rudloff, Elke; Hopper, Kate (Frontiers in Veterinary Science, 2021)
This manuscript will review crystalloid (hypo-, iso-, and hyper-tonic) and colloid (synthetic and natural) fluids that are available for intravenous administration with a focus on their electrolyte, acid-base, colligative, and rheological effects as they relate to each solution's efficacy and safety. The goal is for the reader to better understand the differences between each fluid and the influence on plasma composition, key organ systems, and their implications when used therapeutically in animals with critical illness.